Thyroid autoimmunity is associated with hypothyroid-like symptoms compared with nonautoimmune benign thyroid diseases using a thyroid-specific questionnaire - Tamer M Elsherbiny (SpringerOpen, 2019)
Background Autoimmune hypothyroidism, also commonly known as Hashimoto thyroiditis (HT), is the most common cause of hypothyroidism in iodine-replete areas. Thyroid autoimmunity was shown to be associated with lower quality of life, higher symptom load, and poor physical and psychological well-being. The aim of this study is to evaluate the disease burden of HT using a thyroid-specific questionnaire, the thyroid patient reported outcomes (ThyPRO). Patients and methods The study included 194 patients, divided into two groups: group 1 included 124 patients with HT stable in euthyroidism 6 months before inclusion in the study, and group 2 included 70 patients with euthyroid benign thyroid disease other than HT. All patients completed a professionally translated, carefully revised version of the ThyPRO questionnaire into Arabic language. All patients had their thyroid stimulating hormone (TSH) measured at inclusion. Anti-thyroperoxidase and/or anti-thyroglobulin antibodies were recorded for each patient where available. Results There were no significant differences between the two studied groups regarding age, sex, and TSH. Both anti-thyroperoxidase and anti-thyroglobulin antibodies were significantly higher in HT group versus group 2. Group 1, HT group, showed significantly higher score in the hypothyroid symptom scale compared with group 2. No significant differences were found regarding the remaining symptom scales. Within hypothyroid symptom score scale, group 1 showed significantly higher scores in dry skin and swollen hands and feet items but not in cold sensitivity and itchy skin questions. Conclusion This study showed that thyroid autoimmunity, independent of thyroid function status, is associated with hypothyroid-like symptoms compared with benign thyroid disease other than HT. This may be caused by a direct or an indirect role of thyroid autoantibodies.